Ekofeminisme Chipko Movement, Interkonektivitas Dengan Gerakan Saput Poleng di Bali sebagai Operasionalisasi Pelestarian Alam Berbasis Ibuisme Dalam Kosmologi Hindu - Anggraini, Putu Maria Ratih; Suka Ardiyasa, I Nyoman (Jurnal Penelitian Agama Hindu, 2025)
The Chipko Movement represents an ecological movement initiated by a group of Indian women, driven by the activities of forest environmental destruction. This effort then transformed into an environmental advocacy movement. This practice has the same linearity as the Balinese Hindu community. The way to implement the local community's version of cosmology is through saput poleng (a black-and-white cloth) and the internalization of the Mother Earth concept. The aim of this research is to analyze environmental preservation initiated by local movements, thereby contributing to ecological practices. This research applies the method of intertextuality by analyzing the Chipko Movement and saput poleng. Chipko Movement is interpreted as an affirmation of women as individuals who share responsibility in preserving the environment. This reality is seen from the consistency in protecting forest areas from logging activities. This movement is also implemented in actions to preserve land and forests, as forests and land are considered substantive components of society. The Chipko Movement represents a form of social struggle by the local population, which then transformed into ecological awareness to protect forest areas. The movement has a correlation with saput poleng in Bali, as a way to protect vital areas such as forests by wrapping cloth with circular patterns, with the aim of preserving the ecosystem as a central arena in human life. Wrapping the linear saput poleng with a vision of environmental preservation based on matrilineal principles, emphasizing that women become agents with an extension as tummerfrauen. In conclusion, the Chipko Movement and saput poleng, with differentiated loci, share the same typology, namely associating nature as the personification of mother.